2009
DOI: 10.1515/eqc.2009.243
|View full text |Cite
|
Sign up to set email alerts
|

Quartile Double Rankled Set Sampling for Estimating the Population Mean

Abstract: Quartile Double Ranked Set Sampling (QDRSS) is investigated for estimating the population mean. The QDRSS estimators are compared to the simple random sampling (SRS), ranked set sampling (RSS) and quartile ranked set sampling (QRSS) estimators. It is shown that, the QDRSS estimators are unbiased for the population mean when the underlying distribution is symmetric, and have small biases when the underlying distribution is asymmetric. It turns out that the QDRSS is superior to the SRS, RSS and QRSS based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…For m = 5, we have to select 25 units from the population and then measure only 5 units of them to be a neoteric ranked set sample, which are Y [3] , Y [8] , Y [13] , Y [18] , Y [23] . Therefore, the NRSS mean estimator is…”
Section: Uniform Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…For m = 5, we have to select 25 units from the population and then measure only 5 units of them to be a neoteric ranked set sample, which are Y [3] , Y [8] , Y [13] , Y [18] , Y [23] . Therefore, the NRSS mean estimator is…”
Section: Uniform Distributionmentioning
confidence: 99%
“…Al-Saleh and Al-Omari [5], Al-Omari and Al-Saleh [3] and Al-Omari [1], [2] proposed some mean estimators in other variations of the RSS. Stokes [20] suggested an estimator of the population variance based on RSS and showed that it is asymptotically (n → ∞ or k → ∞) unbiased of the population variance and has greater efficiency than the sample variance using SRS regardless of the issue of ranking.…”
Section: Introductionmentioning
confidence: 99%